The relationship between Parkinson’s disease and gastrointestinal diseases - Zeng, Jiaqi; Wang, Xinchan; Pan, Fei; Mao, Zhiqi (Frontiers in Aging Neuroscience, 2022)
An increasing number of studies have provided evidence for the hypothesis that the pathogenesis of Parkinson’s disease (PD) may derive from the gut. Firstly, Lewy pathology can be induced in the enteric nervous system (ENS) and be transported to the central nervous system (CNS) via the vagal nerve. Secondly, the altered composition of gut microbiota causes an imbalance between beneficial and deleterious microbial metabolites which interacts with the increased gut permeability and the gut inflammation as well as the systemic inflammation. The activated inflammatory status then affects the CNS and promotes the pathology of PD. Given the above-mentioned findings, researchers start to pay attention to the connection between PD and gastrointestinal diseases including irritable bowel syndrome, inflammatory bowel disease, microscopic colitis, gastrointestinal neoplasms, and colonic diverticular disease. This review focuses on the correlation between PD and gastrointestinal diseases as well as the pathogenesis of PD from the gut.